Transplant Hepatic Artery Stenosis: Endovascular Treatment and Complications - Molvar, Christopher; Ogilvie, Ross; Aggarwal, Deep; Borge, Marc (Seminars in Interventional Radiology, 2019)
Hepatic artery stenosis (HAS) is an infrequent complication of liver transplant; if left untreated, it can lead to hepatic artery thrombosis with high risk of biliary necrosis and graft loss. HAS is diagnosed with screening Doppler ultrasound, together with computed tomography angiography and magnetic resonance angiography. Endovascular treatment with angioplasty ± stent placement is safe and effective with infrequent major complications; however, when complications occur, they can devastate long-term graft survival. Herein, we present two cases of HAS treated with balloon angioplasty with resultant major complications requiring operative intervention.
Keywords: hepatic artery; transplant; stenosis; endovascular; angioplasty; complications; interventional radiology